SOME RESULTS ON THE SUBORDINATION PRINCIPLE FOR ANALYTIC FUNCTIONS - Bülent Nafi Örnek (Journal of Amasya University the Institute of Sciences and Technology)
The aim of this paper is to introduce the class of the analytic functions called and to investigate the various properties of the functions belonging this class. For the functions in this class, some inequalities related to the angular derivative have been obtained.